The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00401-012-0950-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectural alterations are widespread in cerebral cortex in tuberous sclerosis complex

Abstract: Tubers are cerebral cortical developmental malformations associated with epilepsy and autism in tuberous sclerosis complex (TSC). The disparity between tuber number and severity of neurological impairment often observed in TSC led us to hypothesize that microscopic structural abnormalities distinct from tubers may occur in TSC. Serial frontal to occipital lobe sections were prepared from five postmortem TSC brain specimens. Sections were probed with cresyl violet stain or NeuN antibodies to define cytoarchitec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 24 publications
4
43
0
Order By: Relevance
“…Furthermore, several studies using MRI diffusion techniques revealed diffuse alterations in the so-called normally appearing WM [3,4], but the relation between WM alterations and neurologic phenotype remains to be clarified. WM alterations seen by MRI studies are in good agreement with diffuse microstructural WM abnormalities found in neuropathological studies in individuals with TSC, reflecting axonal disorganization, reduced/altered myelination, or gliosis [5][6][7]. WM alterations might result from the dysregulation of the mTOR pathway, which is responsible for abnormal connectivity as well as for altered axonal growth [8][9][10].…”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, several studies using MRI diffusion techniques revealed diffuse alterations in the so-called normally appearing WM [3,4], but the relation between WM alterations and neurologic phenotype remains to be clarified. WM alterations seen by MRI studies are in good agreement with diffuse microstructural WM abnormalities found in neuropathological studies in individuals with TSC, reflecting axonal disorganization, reduced/altered myelination, or gliosis [5][6][7]. WM alterations might result from the dysregulation of the mTOR pathway, which is responsible for abnormal connectivity as well as for altered axonal growth [8][9][10].…”
Section: Introductionsupporting
confidence: 79%
“…The observed physiologic and imaging phenomena, the presence of robust MEPs from nTMS stimulation and preserved CS tracts identified by DTI tractography, within the tuber tissue in our patient provide functional and structural support of the intermixing of tuber and functional tissue. This is in agreement with current pathological [4], [26] diffusion imaging [27], and with physiological evidence of widespread and variable degrees of pathology in TSC [28], [29], [30], [31].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies with mouse models of TSC (Meikle et al, 2008; Carson et al, 2012, 2013) suggested that global diffuse changes in white matter might give rise to universal cortical dysfunction together with various neuropsychiatric conditions, in addition to the multifocal tuber pathology. Indeed, Marcotte et al (2012) demonstrated widespread microstructural alterations distinct from tubers in human patients via histological analysis of post-mortem brain specimen. This ex-vivo MRI study with conditional knockouts of Rictor and Tsc2 in Olig2-Cre mice has shown that the developed technique is capable of discovering non-tuber white matter abnormalities, e.g.…”
Section: Discussionmentioning
confidence: 99%